1996
DOI: 10.1071/ch9960951
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Intramolecular Interactions of 2-Methyl-3-(2-Methylphenyl)but-1-ene-1,1-dicarbonitrile (MMBD)

Abstract: 2-Methyl-3-(2-methylphenyl)but-1-ene-1,1-dicarbonitrile (MMBD) has been synthesized from 3-(o-tolyl)butan-2-one. The crystal and molecular structure of this compound was solved by X-ray diffraction, with estimated standard deviations ≤ � 0.005 Ǻ for bond lengths, and ≤ 0.3° for bond angles. Intramolecular interactions of the C≡N group, i.e. of the C-H...N, C-H...π (electrons) and C-H...C type, were observed, and the possibility of weak intramolecular hydrogen bridges in the molecule of MMBD was considered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As is widely known, hydrogen-bonded complexes formed by p bonds and proton donors are thus stabilized by the formation of pÁ Á ÁH hydrogen bonds. [249][250][251][252][253][254][255][256][257] However, this statement was not entirely accepted at first, and thereby various works were elaborated in order to discover whether individual atoms or p-electrons can be really considered protons acceptors. In this scenery the neutron diffraction analysis has shown that pÁ Á ÁH interactions are aligned directly at the midpoint of the p bond.…”
Section: Boaz Galdino De Oliveiramentioning
confidence: 99%
“…As is widely known, hydrogen-bonded complexes formed by p bonds and proton donors are thus stabilized by the formation of pÁ Á ÁH hydrogen bonds. [249][250][251][252][253][254][255][256][257] However, this statement was not entirely accepted at first, and thereby various works were elaborated in order to discover whether individual atoms or p-electrons can be really considered protons acceptors. In this scenery the neutron diffraction analysis has shown that pÁ Á ÁH interactions are aligned directly at the midpoint of the p bond.…”
Section: Boaz Galdino De Oliveiramentioning
confidence: 99%
“…Suttor has found C−H···Y H-bonds in some organic crystal structures, and the possibility that a C−H bond with a nonelectronegative carbon atom acts as a proton donor was commonly accepted after the appearance of the study of Taylor and Kennard . X−H···C, X−H···π-electrons, or even C−H···C/π interactions have been also detected and classified as hydrogen bonds. ,, It was pointed out that C−H···Y H-bonds are weak, but electrostatic forces act far beyond the most often applied van der Waals cutoff; hence, the criterion that the H···Y distance should be less than the sum of van der Waals radii fails . The statement that the X−H proton donating bond is elongated within the hydrogen bridge is also not always fulfilled since systems where the proton donating bonds are shortened were found .…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions are known as nonconventional hydrogen bonds. There are different types of nonconventional hydrogen bonds, for example, H‐bonds with CH bonds as unconventional donors 5–12, those with unconventional acceptors (π electrons within aromatic systems or the other π‐electronic moieties or simple C‐atoms) 13–17, hydrogen bonds with unconventional donors and unconventional acceptors such as CH···C (or CH···π) systems 18–24 and dihydrogen bonds 25–34.…”
Section: Introductionmentioning
confidence: 99%